Exercise and COVID-19: exercise intensity reassures immunological benefits of post-COVID-19 condition - Thirupathi, Anand; Yong, Wang; Oflaz, Ofcan; Agascioglu, Eda; Gu, Yaodong (Frontiers in Physiology, 2023)
Any form of physical activity, including exercise, has various benefits, from shaping physiological functions to combating infections. Simultaneously, the infectivity ratio could reduce physical activity, such as performing habitual exercise. Therefore, immediate attention is necessary. This scenario alters various physiological functions that normally require adaptation to different exercise strategies. However, the intensity and duration associated with this adaptation mechanism but the amount or level required to induce this has not been established well. For example, lower intensity to moderate intensity perhaps failed to induce this adaptive process, while high intensity compromises immune health, which causes to increase in the infection rate. However, high intensity with shorter time produces various morphological alterations in the primary organs, such as the lungs and heart, which facilitate life support in COVID-19 patients. Owing to the less information about exercise protocols failed to assure the benefits of exercise to COVID-19 patients. Therefore, this review will answer how exercise intensity is crucial to reassure the exercise benefits for promoting safe participation during the COVID-19 pandemic.